Nanotubos de titanatos aplicados como sensores de gás - Diego Carvalho Barbosa Alves (2009)
In this work, the application of titanate nanotubes (TNTs) as gas sensors is investigated. TNTs were synthesized by refluxing a TiO2 (anatase) suspension in an aqueous NaOH (10 M) solution for 24hr, followed by washing with water until neutralization. Characterization by X-ray diffraction and scanning and transmission electron microscopiesrevealed that the produced material is sodium trititanate (Na2Ti3O7) and that its morphology consists of entangled tubular filaments. TNT films were prepared by tape casting by using a mixture of TNT with a polymeric binder (polyvinylidene fluoride) and dimethylformamide. A systematic study of the electrical response of devices made by TNT films depositedover Si/SiO2 wafers with interdigitated contacts was performed. The devices were measured in atmosphere of H2 diluted in N2, with concentration ranging from 100 to 5000 ppm, and at temperatures ranging from 20 to 250ºC. In order to enable this study, severalimprovements in the measuring apparatus were implemented. The sensors presented a very promissing performance, showing good sensibility, stability and reproducibility. An interesting result is that the largest sensitivity was observed at ~ 25ºC. For 100 ppm a value of 20% for the sensitivity was obtained. The films sensitivity shows a peculiar dependence on temperature, presenting one maximum at 25ºCand a second one at 150-180ºC. The analysis of the temperature dependence of the film condutivity suggests that two kinds of electrical transport ocurr. For temperatures (T) higher than 100ºC, a thermally activated electronic transport is dominant (activationenergy: 0.56 eV). For T < 100ºC, the conductivity seems to be influenced by the presence of water moluces physisorbed at the surface, suggesting that protonic transport is dominant at low T. Such change in the conduction mechanism might be associated with the variations on the TNT film sensitivity with T